1997
DOI: 10.1007/s005850050437
|View full text |Cite
|
Sign up to set email alerts
|

Improved analysis of plasmasphere motion using the VLA radio interferometer

Abstract: Abstract.Observations using the very large array (VLA) radio interferometer during the past five years have enabled the discovery of a new type of plasmasphere disturbance, the magnetic eastward-directed wave. Previous work indicated these disturbances were likely frozen to the geomagnetic field as determined from their azimuth distributions. This work provides a method to explain more accurately the azimuth distribution, thereby allowing the calculation of the disturbances' location in the plasmasphere indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 9 publications
7
20
0
Order By: Relevance
“…For instance, co-rotation within the plasmasphere will yield an observed speed for such irregularities of 150 m s À1 for heights of about 2000 km. For these observations, this corresponds to a McIlwain L-parameter of about 2.1, which is typical for the irregularities previously discovered with the VLA [Hoogeveen and Jacobson, 1997]. These disturbances will be discussed further in section 5.…”
Section: Multisource 3-d Spectrasupporting
confidence: 62%
“…For instance, co-rotation within the plasmasphere will yield an observed speed for such irregularities of 150 m s À1 for heights of about 2000 km. For these observations, this corresponds to a McIlwain L-parameter of about 2.1, which is typical for the irregularities previously discovered with the VLA [Hoogeveen and Jacobson, 1997]. These disturbances will be discussed further in section 5.…”
Section: Multisource 3-d Spectrasupporting
confidence: 62%
“…These properties imply that they are likely located within the plasmasphere and are the same magnetic eastward directed (MED) disturbances discovered by Jacobson and Erickson [1992b] with the VLA. These were described in more detail by Hoogeveen and Jacobson [1997] as relatively long plasmaspheric irregularities stretched along field lines. After 03:00, westward and southwest directed waves begin to dominate the DFT-based azimuth spectra.…”
Section: Spectral Analysis 221 Self-calibration Datamentioning
confidence: 99%
“…Seminal investigations by Jacobson and Erickson [1992a] and Jacobson and Erickson [1992b] used 330 MHz observations with the VLA to identify and explore several wave-like phenomena identified within the data. Follow-up work done by Hoogeveen and Jacobson [1997] showed that a new class of waves found by Jacobson and Erickson [1992a] were located within the plasmasphere. They were shown to essentially be density fluctuations formed perpendicular to magnetic field lines at McIlwain L-parameters between about 1.8 and 4 which co-rotated with the plasmasphere with a moderate amount of (mostly) westward convection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma was inferred to reside between 2000-and 10,000-km altitude on magnetic L shells of L = 2 -3. Hoogeveen and Jacobson [1997] subsequently demonstrated that the plasma was not actually ''frozen on'' the field lines but was often convected westward or eastward across the field lines. They argued that the restricted range of L shells observed was a limitation of the instrumentation and observations rather than the physics of the plasmasphere.…”
Section: Introductionmentioning
confidence: 99%